2019
DOI: 10.1186/s40659-019-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin induces apoptosis through mitochondrial pathway and PI3K/Akt/mTOR signaling in human non-small cell lung cancer A549 cells

Abstract: Background Currently, the prognosis of patients with non-small cell lung cancer (NSCLC) remains dismal; hence, it is critical to identify effective anti-NSCLC agents with limited side effects. This study aimed to evaluate the therapeutic potential of flavonoid compound vitexin in human NSCLC cells and the underlying mechanisms. Results The experimental results indicated that vitexin reduced the viability of A549 cells in a dose-dependent manner with nearly no toxicity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(52 citation statements)
references
References 19 publications
(17 reference statements)
1
48
0
Order By: Relevance
“…PI3K-AKT-mTOR is one of the major intracellular pathways, which serve a critical regulatory role among different kinds of tumor. mTOR is a key kinase of PI3K/ AKT downstream, it could regulate tumor cell proliferation, growth, survival and angiogenesis [42][43][44]. mTOR protein being proved to be regulated by two pathways.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K-AKT-mTOR is one of the major intracellular pathways, which serve a critical regulatory role among different kinds of tumor. mTOR is a key kinase of PI3K/ AKT downstream, it could regulate tumor cell proliferation, growth, survival and angiogenesis [42][43][44]. mTOR protein being proved to be regulated by two pathways.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, vitexin has been shown to reduce the viability of adenocarcinomic human alveolar basal epithelial cells dose-dependently, with virtually no toxicity to normal human bronchial epithelial cells. Vitexin induced apoptosis in these cells by increasing pro-apoptotic protein expression, reducing mitochondrial membrane potential and through Akt signalling [398]. In a melanoma model, vitexin inhibited growth in vitro and in vivo, arrested the cell cycle in G2/M phase, induced apoptosis, caused DNA damage, and increased ROS accumulation.…”
Section: Vitexin and Isovitexinmentioning
confidence: 98%
“…These results collectively demonstrated that betulinic acid might be a potential and valuable mTOR inhibitor with hypo-toxicity in pancreatic cancer. As a valuable cancer therapy targets, mTOR signaling pathway has mainly modulated cancer cell autophagy or induced apoptosis [26,27]. The nutritional status, growth factor and other environmental stresses caused by mTORC1 complex can inhibit autophagy process to affect cancer cells [28].…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional status, growth factor and other environmental stresses caused by mTORC1 complex can inhibit autophagy process to affect cancer cells [28]. Recently, the mTOR signaling pathway has also been reported to induce the apoptosis of non-small lung cancer [26], esophageal cancer [29] and myeloid leukemia cancer [30]. Nevertheless, the exact molecular mechanism of mTOR signaling regulated by betulinic acid in pancreatic cancer remains unclear.…”
Section: Discussionmentioning
confidence: 99%